THE WORLD MARKET OF EDUCATIONAL SERVICES OF HIGHER SCHOOL - K. Balkizova (Вестник университета)
The article defines the education role in the economic development of the state. The author points out that the sustainable socio-economic development, growth of competitiveness, strengthening the positions on the world market and in the world economic community depend on the formation and improvement of the country's educational potential. The article also considers the reasons for the inclusion of higher education in the system of market relations and the indicators of the activity coverage assessment of the international educational market. Also there are analyzed the key indicators’ changes that reflect the main directions of export of educational services in the leading exporting countries.